1998
DOI: 10.1159/000013783
|View full text |Cite
|
Sign up to set email alerts
|

Subdivisions of AuditoryCortex and Levels of Processing in Primates

Abstract: In a series of experiments on New World and Old World monkeys, architectonic features of auditory cortex were related to tone frequency maps and patterns of connections to generate and evaluate theories of cortical organization. The results suggest that cortical processing of auditory information involves a number of functionally distinct fields that can be broadly grouped into four or more levels of processing. At the first level, there are three primary-like areas, each with a discrete pattern of tonotopic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(50 citation statements)
references
References 50 publications
4
46
0
Order By: Relevance
“…The hierarchical theory of cortical processing (Felleman and Van Essen 1991; Mineault et al 2012; Zeki and Shipp 1988) posits that neural networks in more central auditory cortical areas encode progressively more complex features of the stimulus, increasing their preference for complex, specific acoustic objects, such as vocalizations (Hackett 2011; Kaas and Hackett 1998; Leaver and Rauschecker 2010; Recanzone 2008; Rouiller et al 1991; Ter-Mikaelian et al 2007). Indeed, for some species, including the nonhuman primate, it has been shown that neurons in A1 respond more strongly to the original rather than temporally transformed (compressed or dilated) vocalizations (Wang 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The hierarchical theory of cortical processing (Felleman and Van Essen 1991; Mineault et al 2012; Zeki and Shipp 1988) posits that neural networks in more central auditory cortical areas encode progressively more complex features of the stimulus, increasing their preference for complex, specific acoustic objects, such as vocalizations (Hackett 2011; Kaas and Hackett 1998; Leaver and Rauschecker 2010; Recanzone 2008; Rouiller et al 1991; Ter-Mikaelian et al 2007). Indeed, for some species, including the nonhuman primate, it has been shown that neurons in A1 respond more strongly to the original rather than temporally transformed (compressed or dilated) vocalizations (Wang 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The atlas surface from the macaque F99 atlas which is available in Caret software (Van Essen et al, 2001) was co-registered with our surfaces using ICP (Iterative Closest Point) registration (affine registration) as implemented in vtk (www.vtk.org). The benefit of this local surface-based registration is to enable the comparison of our functional MRI results with the anatomical atlas (Markov et al, 2011) which uses the well-established nomenclature and subdivisions of the auditory cortex defined earlier (Hackett et al, 1998; Kaas and Hackett, 1998). To improve the visibility of the cortical surface we flattened the superior temporal plane.…”
Section: Methodsmentioning
confidence: 99%
“…Information is sent up from the cochlea to the cortex via roughly half a dozen brainstem areas (Kandel et al, 2000), incorporating receptive fields with monaural or binaural representations conveying spatial location and increasing selectivity for various combinations of spectral and temporal signal information. The receptive field properties of auditory neurons similarly build-up in complexity and specificity along the cortical mantle to represent objects and action events (Rauschecker et al, 1995, 1997; Kaas and Hackett, 1998). Representations of sound at the level of primary auditory cortex proper maintains at least a roughly tonotopic organization in humans (Wessinger et al, 1997; Formisano et al, 2003), and neuropsychological studies indicate that information must reach this stage for normal bottom-up conscious awareness of sound and auditory object perception (Engelien et al, 2000).…”
Section: Bottom-up Perspectives Of Vision and Hearing Modelsmentioning
confidence: 99%
“…Representations of sound at the level of primary auditory cortex proper maintains at least a roughly tonotopic organization in humans (Wessinger et al, 1997; Formisano et al, 2003), and neuropsychological studies indicate that information must reach this stage for normal bottom-up conscious awareness of sound and auditory object perception (Engelien et al, 2000). Auditory “core” regions of cortex receive strong thalamic inputs, are tonotopically organized, and thus generally regarded as primary auditory cortices (Kaas and Hackett, 1998; Sweet et al, 2005). These primary auditory regions send information on to higher hierarchical stages, which in macaques are termed “belt” and “parabelt” regions that surround the core (Rauschecker et al, 1995; Kaas and Hackett, 1998, 2000a; Rauschecker, 1998).…”
Section: Bottom-up Perspectives Of Vision and Hearing Modelsmentioning
confidence: 99%
See 1 more Smart Citation